2020
DOI: 10.1051/0004-6361/202037904
|View full text |Cite
|
Sign up to set email alerts
|

Formation pathways of complex organic molecules: OH projectile colliding with methanol ice mantle (CH3OH)10

Abstract: In this article, we simulated the collisions of an OH• projectile impacting on a methanol cluster formed by ten units of methanol to mimic an ice mantle (CH3OH)10. The chemical processes occurring after the impact were studied through Born-Oppenheimer (ab-initio) molecular dynamics. We focus on collisions with initial kinetic impact energy of 10–22 eV, where the richest chemistry happens. We report the formation mechanisms of stable complex organic molecules (COMs) such as methoxymethanol CH3OCH2OH, formic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…This cluster was hit by an OH + projectile mimicking an interstellar dust grain covered only by methanol molecules. Moreover, a comparison of these results was made with the previous process observed after the impact of OH -, OH • , and OH + projectiles (Inostroza et al 2019;Inostroza-Pino et al 2020. Density functional theory calculations under a micro-canonical ensemble (NEV ensemble) were performed with the hybrid functional of Head-Gordon ωB97X-D (Helgaker et al 1990;Uggerud & Helgaker 1992;Bolton et al 1998;McBride et al 2013) and the Pople Basis Set 6-31+g(d,p) (Gordon 1982;Check et al 2001;Borrás-Almenar et al 2001).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This cluster was hit by an OH + projectile mimicking an interstellar dust grain covered only by methanol molecules. Moreover, a comparison of these results was made with the previous process observed after the impact of OH -, OH • , and OH + projectiles (Inostroza et al 2019;Inostroza-Pino et al 2020. Density functional theory calculations under a micro-canonical ensemble (NEV ensemble) were performed with the hybrid functional of Head-Gordon ωB97X-D (Helgaker et al 1990;Uggerud & Helgaker 1992;Bolton et al 1998;McBride et al 2013) and the Pople Basis Set 6-31+g(d,p) (Gordon 1982;Check et al 2001;Borrás-Almenar et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory calculations under a micro-canonical ensemble (NEV ensemble) were performed with the hybrid functional of Head-Gordon ωB97X-D (Helgaker et al 1990;Uggerud & Helgaker 1992;Bolton et al 1998;McBride et al 2013) and the Pople Basis Set 6-31+g(d,p) (Gordon 1982;Check et al 2001;Borrás-Almenar et al 2001). As Inostroza-Pino et al did in 2020 and 2021, we divided a sphere symmetrically to obtain 24 initial impact positions (Inostroza-Pino et al 2020). For each hit, the species were in their ground state and the projectile always faced the center of mass of the (CH 3 OH) 10 ice mantle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, this would provide a pathway towards ribose, a compound of direct biological relevance. In the recent past, several studies have been published focusing on solid-state MM formation pathways through energetic processing of CH 3 OH ice or CH 3 OH-containing ices (Maity et al 2015;Paardekooper et al 2016;Schneider et al 2019;Inostroza-Pino et al 2020). These studies demonstrated that it is possible to form MM under UV light photolysis or upon cosmic rays bombardment.…”
Section: Introductionmentioning
confidence: 99%